Analysing leisure cards from a buyers' perspective – a case study for the leisure card Tyrol. Issue 6 (2nd November 2021) - Seidl, Maximilian; Schnitzer, Martin
ABSTRACT: Purpose: While tourism cards are quite common, leisure cards are less popular, especially with respect to scholarly research. This study sheds light on leisure cards by analysing a card covering a wide choice of leisure activities in the most populated area in Tyrol, Austria. Methodology: As research lacks insight particularly into the buyers' perspective, an explorative approach including qualitative interviews ( n  =   7) and an online survey ( n   =    2391) was chosen. Findings: Data raised suggests the main reasons for purchasing the card include easier access to sports and low price compared to single tickets for attractions. Practical implications: The perceptions of buyers and suppliers basically coincide in terms of the card's added value. Overall, the results lend themselves as an initial point of reference for future deliberations. Research Contribution: This study provides a first insight into the added value of a possibly sustainable and arguably (economically) stable card scheme and thus opens further research opportunities.